Perancangan dan Implementasi Sistem Pendataan Kasus Tindak Pidana - Ryan Aji Wijaya; Angga Dri Hananto; Adimas Rexsi Saputra (Sienna, 2022)
North Lampung Police has a vision of realizing a professional, moral, modern, superior and trustworthy Police Police of North Lampung in order to support the creation of a sovereign, independent and personable Indonesia based on mutual cooperation. And to realize this vision, the North Lampung Police have several missions, one of which is to realize the sustainable use of technology and police data systems that are integrated in the North Lampung Police Station area, which is supported by scientific studies and studies, in order to further optimize the performance of the Police. Based on the results of the competition above, the researcher won 3rd place with the title "Collecting Criminal Cases". The prototype that was produced from the competition, the researchers implemented it in the form of research with the title "Design and implementation of a data collection system for criminal cases". To solve this problem, the researcher used the prototype method. With steps 1. Listening to user needs, 2. Designing samples or Mock-ups, 3. Testing samples or Mock-ups. From the results of testing applications by users in the form of admin login pages, admin menu pages, user list pages on admins, investigator data pages on admins, user login pages, user menu pages, and case addition pages by users, it can be concluded that the data collection application for criminal cases runs smoothly. good.